Multi-core processor scheduling with respect to the mutual influence of jobs - Eremeev, Anton V.; Sakhno, Maria Yu. (Numerical Methods and Programming (Vychislitel’nye Metody i Programmirovanie), 2023)
The paper deals with the problem of multi-core processor scheduling with respect to the mutual influence of jobs during their joint execution. A problem formulation and a model of mixed integer linear programming are proposed, the problem is shown to be NP-hard with the number of cores bounded by a constant. The results of the Intel TBB scheduler and the greedy algorithm are compared with the results obtained in accordance with the proposed model using the CPLEX package. The conducted experiment showed the advantages of the proposed approach in terms of the completion time of all jobs.